Pengaruh Leverage dan Profitabilitas terhadap Harga Saham pada Perusahaan Sub Sektor Konstruksi dan Bangunan yang Terdaftar di Bursa Efek Indonesia Periode 2017-2019 - Dinda Nadia; Gede Putu Agus Jana Susila (Jurnal Akuntansi Profesi, 2021)
This study aims to examine and determine the effect of leverage and profitability on stock prices simultaneously and partially. The design of this research was causal quantitative research. The subject of this research is the construction and building sub-sector companies listed on the Indonesia Stock Exchange and the objects of this research were leverage, profitability, and stock prices. The sampling technique was purposive sampling with a total of 15 companies. Data were collected by recording documents, then analyzed using multiple linear regression analysis. The results showed that (1) leverage and profitability simultaneously had a significant effect on stock prices of 52.2%, (2) leverage partially had a positive and significant effect on stock prices of 51.4%, (3) partially profitability had a positive effect and not significant to the stock price of 1.5%.